School Violence, Depressive Symptoms, and Help-seeking Behavior: A Gender-stratified Analysis of Biethnic Adolescents in South Korea - Ji-Hwan Kim; Ja Young Kim; Seung-Sup Kim (Korean Society for Preventive Medicine, 2016)
Objectives: In South Korea (hereafter Korea), the number of adolescent offspring of immigrants has rapidly increased since the early 1990s, mainly due to international marriage. This research sought to examine the association between the experience of school violence and mental health outcomes, and the role of help-seeking behaviors in the association, among biethnic adolescents in Korea. Methods: We analyzed cross-sectional data of 3627 biethnic adolescents in Korea from the 2012 National Survey of Multicultural Families. Based on the victim's help-seeking behavior, adolescents who experienced school violence were classified into three groups: 'seeking help' group; 'feeling nothing' group; 'not seeking help' group. Multivariate logistic regression was applied to examine the associations between the experience of school violence and depressive symptoms for males and females separately. Results: In the gender-stratified analysis, school violence was associated with depressive symptoms in the 'not seeking help' (odds ratio [OR], 7.05; 95% confidence interval [CI], 3.76 to 13.23) and the 'seeking help' group (OR, 2.77; 95% CI, 1.73 to 4.44) among male adolescents after adjusting for potential confounders, including the nationality of the immigrant parent and Korean language fluency. Similar associations were observed in the female groups. However, in the 'feeling nothing' group, the association was only significant for males (OR, 8.34; 95% CI, 2.82 to 24.69), but not females (OR, 0.77; 95% CI, 0.18 to 3.28). Conclusions: This study suggests that experience of school violence is associated with depressive symptoms and that the role of victims' help-seeking behaviors in the association may differ by gender among biethnic adolescents in Korea.